Reflections of functional training on shooters' grip stability - Chen, T.; Yue, J. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Shooting is a technical sport demanding much control and accuracy from the athletes. Physical fitness is a critical factor for the sport's skill level, and it is believed that functional training can effectively improve the shooter's technical level, ensuring greater athlete stability.